Crystal structure of the Bacillus subtilis phosphodiesterase PhoD reveals an iron and calcium-containing active site. - Rodriguez, F; Lillington, J; Johnson, S; Timmel, C; Lea, S; Berks, B (American Society for Biochemistry and Molecular Biology Inc., 2014)
The PhoD family of extra-cytoplasmic phosphodiesterases are among the most commonly occurring bacterial phosphatases. The exemplars for this family are the PhoD protein of Bacillus subtilis and the phospholipase D of Streptomyces chromofuscus. We present the crystal structure of B. subtilis PhoD. PhoD is most closely related to purple acid phosphatases (PAPs) with both types of enzyme containing a tyrosinate-ligated Fe(3+) ion. However, the PhoD active site diverges from that found in PAPs and uses two Ca(2+) ions instead of the single extra Fe(2+), Mn(2+), or Zn(2+) ion present in PAPs. The PhoD crystals contain a phosphate molecule that coordinates all three active site metal ions and that is proposed to represent a product complex. A C-terminal helix lies over the active site and controls access to the catalytic center. The structure of PhoD defines a new phosphatase active site architecture based on Fe(3+) and Ca(2+) ions.